Peering into Alberta’s Darkening Future: How Oil Prices Impact Alberta’s Royalty Revenues - Sarah Dobson (The School of Public Policy Publications, 2017)
The price of oil just keeps collapsing — and the fate of Alberta’s revenues is buckling with it. Going into March 2015, it seemed as if prices might have finally found a bottom, somewhere between US$48 and US$52. By the second week of March, they began falling again, to the low forties. These are prices the Alberta government had not even ventured to fathom when first putting together its forecasts for the impact of falling oil prices on the province’s finances. Come the fourth quarter of the Alberta government’s 2014/15 fiscal year, the province’s finances will begin to really feel the blow from the plunge in oil, as royalty payments dry up significantly. Come the 2015/16 fiscal year, the situation becomes even bleaker. In fact, the current fiscal year will seem pleasant compared to the next one. Due to a stronger than expected first half of the year, actual bitumen and crude oil royalties collected in Alberta from April to September 2014 exceeded estimates by $1.3 billion. That will mitigate some of the damage that the continuing slide in prices will cause by the year’s end, with the government’s third quarter update showing expected year-end crude oil and bitumen royalty revenues falling short of the budget target by $549 million. So severe has the fall in oil prices been that, in March 2015, the number of barrels of conventional oil that the government collects in royalties could plummet by up to 53,000 barrels from the 2014/15 budget forecast, declining to just 4,100 barrels per day. This suggests that prices may be nearing a point where royalty collection from conventional crude oil production is at risk of being virtually eliminated. Bitumen royalties are not faring much better. Relative to July 2014, per barrel royalties in February 2015 have potentially declined by 60 to 90 per cent.  All told, the combined effect of the changing exchange rate, lower prices, and the lower royalty rates that take effect in this low-price environment, will lead to a potential decline in crude oil and bitumen royalty revenues of 42 to 74 per cent in the 2015/16 fiscal year. This corresponds to a monetary decline of roughly $3.3 billion to $5.8 billion. If oil prices stay below US$45 per barrel, that decline will become even more severe. The pain for Alberta revenues does not end there. The government will be facing additional losses in land sale revenues, natural gas royalties, and tax revenues. Still, even the surprisingly strong revenues for the first half of the year suggest a serious problem with government forecasts. By the end of September, the government had collected $5.198 billion in crude oil and bitumen royalties, 33 per cent higher than originally forecast. That government estimates could be so far off the mark raises serious questions about the methods the province is using to forecast royalties. In a province so dependent on resource royalties for its revenues, adding the unpredictability of unreliable forecasting methods can only put its fiscal planning at that much greater risk of instability.